Mixed Cutaneous Infection Caused by Mycobacterium szulgai and Mycobacterium intermedium in a Healthy Adult Female: A Rare Case Report - Amresh Kumar Singh; Rungmei S. K. Marak; Anand Kumar Maurya; Manaswini Das; Vijaya Lakshmi Nag; Tapan N. Dhole (Case Reports in Dermatological Medicine)
Nontuberculous mycobacteria (NTMs) are ubiquitous and are being increasingly reported as human opportunistic infection. Cutaneous infection caused by mixed NTM is extremely rare. We encountered the case of a 46-year-old female, who presented with multiple discharging sinuses over the lower anterior abdominal wall (over a previous appendectomy scar) for the past 2 years. Microscopy and culture of the pus discharge were done to isolate and identify the etiological agent. Finally, GenoType Mycobacterium CM/AS assay proved it to be a mixed infection caused by Mycobacterium szulgai and M. intermedium. The patient was advised a combination of rifampicin 600 mg once daily, ethambutol 600 mg once daily, and clarithromycin 500 mg twice daily to be taken along with periodic follow-up based upon clinical response as well as microbiological response. We emphasize that infections by NTM must be considered in the etiology of nonhealing wounds or sinuses, especially at postsurgical sites.